2006
DOI: 10.1002/mnfr.200500109
|View full text |Cite
|
Sign up to set email alerts
|

Tea, obesity, and diabetes

Abstract: Tea has been found to possess widespread biological functions based on a variety of laboratory data. The effects of tea on obesity and diabetes have received increasing attention. This paper reviews the evidence for the connections among tea catechins, and obesity and diabetes. Tea catechins, especially (-)-epigallocatechin gallate (EGCG), appear to have antiobesity and antidiabetic effects. While few epidemiological and clinical studies show the health benefits of EGCG on obesity and diabetes, the mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
204
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(219 citation statements)
references
References 148 publications
(367 reference statements)
6
204
0
9
Order By: Relevance
“…The results of the present study clearly indicated that EGCG, which has been shown to improve dysregulation of energy homeostasis (17,18), effectively prevents the development of liver tumorigenesis in obese and diabetic db/db mice by improving hyperinsulinemia and hepatic steatosis. A recent study showed that EGCG suppressed the development of colonic premalignant lesions induced by azoxymethane in db/db mice through improvement of hyperinsulinemia and inhibition of the IGF/IGF-1R axis on the colonic mucosa (16).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…The results of the present study clearly indicated that EGCG, which has been shown to improve dysregulation of energy homeostasis (17,18), effectively prevents the development of liver tumorigenesis in obese and diabetic db/db mice by improving hyperinsulinemia and hepatic steatosis. A recent study showed that EGCG suppressed the development of colonic premalignant lesions induced by azoxymethane in db/db mice through improvement of hyperinsulinemia and inhibition of the IGF/IGF-1R axis on the colonic mucosa (16).…”
Section: Discussionsupporting
confidence: 57%
“…In summary, the prevention of HCC by targeting the IGF/IGF-1R axis, hepatic steatosis, and chronic inflammation, which are caused by dysregulation of energy homeostasis, might represent a promising strategy for obese individuals who are at an increased risk of developing HCC (3,8). GTCs, including EGCG, seem to be potentially effective and critical candidates for this purpose because, as shown in the results of the present study and those from previous reports, these agents can target metabolic abnormalities and may therefore restore metabolic homeostasis (16)(17)(18)(19)(20)(21)(22).…”
Section: Gapdhsupporting
confidence: 61%
See 1 more Smart Citation
“…Increasing evidence suggests that tea flavan-3-ols are beneficial for human health as a result of their antioxidant capacity (Luximon-Ramma et al, 2006), chemopreventive activities against prostate and ovarian cancers (Bemis et al, 2006;Ravindranath et al, 2006), antiobesity and antidiabetic effects (Yang and Koo, 2000;Kao et al, 2006;Wolfram et al, 2006), and cardiovascular disease prevention properties (Yang and Koo, 2000). Tea flavanols, especially catechins, may also play roles in the defense of tea against infection/infestation .…”
mentioning
confidence: 99%
“…The potential health benefits associated with tea consumption have been partially attributed to the antioxidative properties of polyphenols, particularly to catechins, among which EGCG is the most effective. Green tea seems to also have antidiabetic and anti-obesity properties [5]. On the basis of its potential anti-obesity effect, green tea has been marketed during recent years as a herbal supplement for the control of body weight.…”
mentioning
confidence: 99%